Psychosocial Effects of Perceived Emotional Synchrony in Collective Gatherings - Wlodarczyk, A (American Psychological Association Inc., 2015)
In a classic theory, Durkheim (1912) predicted that because of the social sharing of emotion they generate, collective gatherings bring participants to a stage of collective effervescence in which they experience a sense of union with others and a feeling of empowerment accompanied by positive affect. This would lead them to leave the collective situation with a renewed sense of confidence in life and in social institutions. A century after Durkheim s predictions of these effects, though, they remained untested as a whole. This article reports 4 studies, 2 correlational, 1 semilongitudinal, and 1 experimental, assessing the positive effects of participation in either positively valenced (folkloric marches) or negatively valenced (protest demonstrations) collective gatherings. Results confirmed that collective gatherings consistently strengthened collective identity, identity fusion, and social integration, as well as enhancing personal and collective self-esteem and efficacy, positive affect, and positive social beliefs among participants. In line with a central tenet of the theory, emotional communion, or perceived emotional synchrony with others mediated these effects. Higher perceived emotional synchrony was associated with stronger emotional reactions, stronger social support, and higher endorsement of social beliefs and values. Participation in symbolic collective gatherings also particularly reinforced identity fusion when perceived emotional synchrony was high. The respective contributions of perceived emotional synchrony and flow, or optimal experience, were also assessed. Whereas perceived emotional synchrony emerged as strongly related to the various social outcomes, flow was observed to be related first to collective efficacy and self-esteem, and thus, to encompass mainly empowerment effects. © 2014 American Psychological Association.